A taxonomic revision of the genus Edosa Walker, 1886 from China (Lepidoptera, Tineidae, Perissomasticinae) - Yang, Linlin; Wang, Shuxia; Li, Houhun (Zootaxa, 2014)
The genus Edosa Walker, 1886 is revised in China. Of the 31 recognized species, 23 are described as new: Edosa aurea sp. nov., E. baculiformis sp. nov., E. bicolor sp. nov., E. bifurcata sp. nov., E. carinata sp. nov., E. conchata sp. nov., E. cornuta sp. nov., E. curvidorsalis sp. nov., E. dentata sp. nov., E. digitata sp. nov., E. duoprojecta sp. nov., E. elongata sp. nov., E. eminens sp. nov., E. hamata sp. nov., E. longicornis sp. nov., E. minuta sp. nov., E. robinsoni sp. nov., E. robustispina sp. nov., E. semicircularis sp. nov., E. torta sp. nov., E. truncatula sp. nov., E. uncusella sp. nov., and E. varians sp. nov.; Edosa gaedikei nom. nov. is proposed as a replacement name for Edosa spinosa Gaedike, 2012, a junior homonym of Edosa spinosa Gaedike, 1984; four species are newly recorded for China: E. hendrixella Robinson, 2008, E. crayella Robinson, 2008, E. orphnodes (Meyrick, 1911) and E. smithaella Robinson, 2008; the female of E. hendrixella is described for the first time. Phylogenetic relationships of the Chinese species, except E. malthacopis (Meyrick, 1936), are postulated based on 42 morphological characters. The phylogenetic analysis of the morphology matrix yielded one most parsimonious tree (length 121 steps, CI = 0.56, RI = 0.81), based on which seven species-groups are proposed: the hemichrysella-group, the subochraceella-group, the pyrochra-group, the duoprojecta-group, the eminens-group, the crayella-group and the uncusella-group. The whole body structures of the genus are presented and photographs of adults and genitalia are provided, along with a key to all the known Chinese species and maps to show the distribution of Edosa in China. A world checklist of Edosa is given as an appendix, in which 41 new combinations are included.